2008
DOI: 10.1007/s00383-008-2178-9
|View full text |Cite
|
Sign up to set email alerts
|

Late presentation of gastric tube ulcer perforation after oesophageal atresia repair

Abstract: Ulcer formation in intrathoracic grafts after oesophageal replacement is considered an infrequent complication of the procedure. We present a rare case of a gastric tube ulcer with perforation, more than 30 years after gastric tube interposition for oesophageal atresia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
6
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 13 publications
0
6
0
Order By: Relevance
“…None were reported to undergo additional operations for postoperative complications. Hazebroek et al [10] reported a patient with 30 year follow-up after undergoing reverse gastric tube interposition for esophageal atresia. She presented at age 32 years with hematemesis and was found to have a gastric tube ulcer that eventually led to a gastrobronchial fistula.…”
Section: Discussionmentioning
confidence: 98%
“…None were reported to undergo additional operations for postoperative complications. Hazebroek et al [10] reported a patient with 30 year follow-up after undergoing reverse gastric tube interposition for esophageal atresia. She presented at age 32 years with hematemesis and was found to have a gastric tube ulcer that eventually led to a gastrobronchial fistula.…”
Section: Discussionmentioning
confidence: 98%
“…In general, there are three routes of reconstruction after esophagectomy for esophageal cancer: posterior mediastinal, retrosternal, and antesternal. In the posterior mediastinal route, gastric tube perforation generally occurs into the thoracic cavity, which is serious and sometimes fatal 1,5–8 . By contrast, retrosternal‐reconstructed gastric tube perforation is less severe due to the narrow space in the retrosternal cavity 9 .…”
Section: Discussionmentioning
confidence: 99%
“…In the posterior mediastinal route, gastric tube perforation generally occurs into the thoracic cavity, which is serious and sometimes fatal. 1 , 5 , 6 , 7 , 8 By contrast, retrosternal‐reconstructed gastric tube perforation is less severe due to the narrow space in the retrosternal cavity. 9 However, in the present case, due to the repeated gastric tube ulcer recurrence and chronic inflammation, penetration between the gastric tube and pericardium occurred, resulting in retrosternal and pericardial abscess formation.…”
Section: Discussionmentioning
confidence: 99%
“…Extirpation of the esophagus and plastic surgery with the isoperistaltic gastric tube are preferred among a variety of methods for reconstruction in benign esophageal disease [10][11][12]. Studying the delayed consequences of esophagogastroplasty revealed a high risk for the development and progression of pathological changes (despite high functional activity of the gastric tube) [4,5,8,13].…”
mentioning
confidence: 99%